Dense, continent‐wide, molecular and morphological sampling supports old and new taxa in Australian pentaneurine Tanypodinae (Diptera: Chironomidae). Issue 3 (30th August 2021) - Cranston, Peter S; Krosch, Matt
Abstract: The Chironomidae subfamily Tanypodinae in Australia is subject to continuing study in a global context and contains a mix of endemic and widespread genera. The monophyletic, globally diverse genus Larsia Fittkau has been sampled extensively in all life stages throughout Australia, and from the northern hemisphere and South America. Molecular evidence supports a previously 'coded' Australian taxon as its sister group, described here as a new genus, Paralarsia gen. nov., for the single species P. maiwar sp. nov . A shallower and highly sampled Australian cluster allocated to Larsia albiceps Johannsen is redescribed here, substantially conforming to prevailing generic diagnoses in each life stage. The species is common and abundant across Australia, including in ephemeral arid‐zone waters and drainages affected by historic mining. A continent‐wide species for which no cryptic species are revealed by molecular analyses is unusual and counter‐intuitive. Only one morphologically distinctive taxon, from uranium mine‐affected streams in tropical Australia, is recognised as new although in the absence of molecular data: Larsia wakbarrarn sp. nov., based on larva, pupa and pharate adults. Some pupal Larsia from south‐east Asia are differentiated and variation discussed relative to L. albiceps, and some consideration is given to neotropical diversity.